Aldosterone-Related Cardiovascular Disease and Benefits of Mineralocorticoid Receptor Antagonists in Clinical Practice - Maria Alfarano, MD, PhD; Giulia Marchionni, MD; Jacopo Costantino, MD; Federico Ballatore, MD; Romina Verardo, PhD; Fabio Miraldi, MD; Francesco Luigi Ciciarello, MD; Luigi Petramala, MD; Claudio Letizia, MD; Andrea Frustaci, MD; Cristina Chimenti, MD, PhD (JACC: Advances)
High levels of aldosterone are associated with vascular and cardiac remodeling, myocardial fibrosis, and endothelial dysfunction with consequent increased risk of cardiovascular events and cardiovascular mortality. Indeed, mineralcorticoid receptor antagonists (MRAs) are recommended in the treatment of arterial hypertension, heart failure, alone or associated with chronic kidney disease. Nevertheless, molecular pathways underlying aldosterone-induced cardiac remodeling are poorly investigated. High levels of aldosterone induce reactive oxygen species with consequent oxidative stress and mitochondrial dysfunction. Moreover, aldosterone induces myocardial hypertrophy through increase of sarcomere mass mediated by pro-hypertrophic effect mediated by a G protein-coupled receptor kinase 5 cytosolic signaling and retention of ions and water regulated by aquaporins. Aim of this review is to report the data from the literature regarding excessive aldosterone signaling in mediating cardiovascular disease, also highlighting the morphostructural and molecular pathways correlated to myocardial damage and the role of MRAs in clinical practice.